Beats and Ginnsberg - Pokharel, Badri Prasad (Tribhuvan University Journal, 2010)
Every literary movement has a potential to influence the future generation. In this context, the Beat Generation, a literary movement was started shortly after the World War II by some ángry young men’ or rebellious personalities who were seeking another world for the adjustment away from the confinements of the established norms and conventions. The post war period was a time when many people from every nook and corner were in pursuit of liberation in works, life style and other alternate forms of livelihood. ’Beat’ writers, though they didn’t follow the established patterns, were socially and culturally accepted by the then young generation either in the group of ’hippie’, or in the hallucinogenic world. Engaging in norcotic intoxication, Immoral and unsocial activities like gay marriage, homosexuality etc., purposeless wanderings, practicing Eastern religious activities etc. sound, in a sense, completely non sense, but what can be perceived from those above mentioned activities is that the young generation had been fed up with the established terms and conditions and was on the way of exploring new world. In short, the ’Beats’ have shown a way to the aspired youth for an alternate source of creativity.